Investigating the Readiness of EFL Pre-Service Teachers in Implementing Technology-Based Teaching: A Phenomenological Study - Alaka, Anta; Nurhayati, Lusi; Widayanti, Eka; Habiburrahman, Habiburrahman; Kurniawan, Ilham; Amin, Muhammad Safiul (Universitas Pendidikan Mandalika, 2025)
This study aims to investigate EFL pre-service teachers' readiness to use technology in English Language Teaching (ELT) classrooms and identify the factors that influence their readiness. A phenomenological research design was employed, involving 30 final-semester EFL pre-service teachers enrolled in a teacher education program, selected through purposive sampling. Data were collected through open-ended surveys and interviews and analyzed thematically to extract key themes related to readiness, technological competence, and influencing factors. Findings demonstrated a high level of readiness among participants, supported by strong technological competence and confidence. Participants showed proficiency in using Learning Management Systems (LMS), Canva, and game-based applications like Kahoot to create interactive and engaging learning environments. Internal factors (such as self-confidence and technological skills) and external factors (such as institutional support, courses, and workshops) influenced their readiness. The findings provide a framework for enhancing teacher training curricula and suggest ways to improve student engagement and learning outcomes through effective technology integration. This study contributes to the limited literature on technology integration readiness among EFL pre-service teachers in Indonesia.